Caracterización del registro eruptivo de Isla Decepción (Islas Shetland del Sur, Antártida) mediante caracterización de capas de cenizas en testigos oceánicos proximales - Polo-Sánchez, A.; Hopfenblatt, Joaquin; Geyer, Adelina; Aulinas, M.; Ercilla, Gemma; Álvarez-Valero, A. M. (Sociedad Geológica de España, 2021)
X Congreso Geológico de España, 5-7 de julio 2021, Vitoria-Gasteiz.-- 1 page.-- Analyzed tephra samples were provided by the rock repository of the Instituto de Ciencias del Mar del CSIC (ICM-CSIC) (http://gma.icm.csic.es/ca/dades) [EN] Deception Island (South Shetland Islands) is one of the most active volcanoes in Antarctica where a future eruption is very likely to happen. In this work we have performed a physico-chemical characterization of the ash layers found on five marine sediment cores drilled along the Bransfield Strait less than 40 km distance from Deception Island. The final aim is to trace isochronous tephra horizons between the studied cores and try associating them to their respective eruptive events on the island. Results obtained indicate that most of the layers are moderate sorted coarse ash. Minor amounts of lapilli and fine ash appear in the shallower (0 to 50 cm depth) layers. The morphology indicates that the reworking effect by turbiditic currents has not affected the information necessary for correlation and that the eruptions that formed the layers were phreatomagmatic. The longest core (TG-48, 120 cm long) contains 15 layers, the deepest ones (113, 115 and 120 cm depth) may be associated with a period of abundant volcanic activity around 2000 years BP [ES] Isla Decepción (Islas Shetland del Sur), es uno de los volcanes más activos de la Antártida en el que se prevé una alta probabilidad de erupción en un futuro. En el presente trabajo, se ha llevado a cabo la caracterización físico-química de las capas de ceniza halladas en cinco testigos marinos obtenidos a lo largo del Estrecho de Bransfield a menos de 40 km de distancia de Decepción. El objetivo es poder trazar horizontes de la misma edad entre los testigos y asociarlos a sus erupciones respectivas. La mayoría de las capas son ceniza gruesa moderadamente clasificada. Cantidades menores de lapilli y ceniza fina se encuentran en las capas superficiales (0 a 50 cm de profundidad). La morfología indica que el efecto de ...